2014
DOI: 10.1007/s12013-014-0283-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Phenformin in Non-Small Cell Lung Cancer (NSCLC) Ionizing Radiation Treatment

Abstract: Biguanides, used for anti-diabetic drugs, bring more attention in cancer research for their beneficial effects. Phenformin is more potent than metformin. However its potential application as a anti-cancer regent is far behind metformin. In order to investigate any beneficial effect of combination of Phenformin and radiotherapy, non-small cell lung cancer cell lines A549 and H1299 were exposure under different dose of ionizing radiation with or without Phenformin. Results indicated Phenformin showed synergistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…However, there is controversy regarding the role of AMPK in the anti-tumor activity of phenformin. It was reported that phenformin displays AMPK-independent effects on cancer cell proliferation and metabolism [ 29 ], whereas others have shown that the anti-tumor effect of phenformin is dependent, at least partially, on AMPK signaling [ 7 , 10 , 30 ]. Our results demonstrated that AMPK phosphorylation increases in breast cancer cells treated with phenformin.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is controversy regarding the role of AMPK in the anti-tumor activity of phenformin. It was reported that phenformin displays AMPK-independent effects on cancer cell proliferation and metabolism [ 29 ], whereas others have shown that the anti-tumor effect of phenformin is dependent, at least partially, on AMPK signaling [ 7 , 10 , 30 ]. Our results demonstrated that AMPK phosphorylation increases in breast cancer cells treated with phenformin.…”
Section: Discussionmentioning
confidence: 99%
“…Met has been used in the clinic for over 50 years and has a very good safety profile (diabetic patients tolerate daily doses of 2-3 g) (1-4). Efforts to improve and enhance efficacy of Met involved modification of structure by attaching alkyl or aromatic groups (e.g., butformin, phenformin) (17) (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Mito-Met 10 inhibited mitochondrial complex I, stimulating superoxide generation and AMPK activation, more potently than Met in MiaPaCa-2 cells. Reports suggest that Met (1 mM) pretreatment followed by radiation resulted in enhanced cancer cell killing (17-19). In this study, we show that Mito-Met 10 enhanced radiation sensitivity in PDAC to the same extent as did Met (1 mM) but at a 1,000-fold lower concentration (1 μM).…”
Section: Introductionmentioning
confidence: 99%
“…The biguanides metformin (METF) and phenformin (PHEN) are anti-diabetic drugs, but intriguingly, biguanides decrease cancer incidence and cancer-related mortality 1 , 2 . Preclinical studies have demonstrated that biguanides inhibit cancer cell proliferation 3 5 , and may potentiate conventional treatment 4 , 6 9 . METF has an excellent safety profile and is the first-line drug for managing type 2 diabetes, and exploring its significance in oncology is appealing.…”
Section: Introductionmentioning
confidence: 99%